2023
DOI: 10.3389/fpls.2023.1166140
|View full text |Cite
|
Sign up to set email alerts
|

Progress, challenge and prospect of plant plastome annotation

Abstract: The plastome (plastid genome) represents an indispensable molecular data source for studying phylogeny and evolution in plants. Although the plastome size is much smaller than that of nuclear genome, and multiple plastome annotation tools have been specifically developed, accurate annotation of plastomes is still a challenging task. Different plastome annotation tools apply different principles and workflows, and annotation errors frequently occur in published plastomes and those issued in GenBank. It is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…While gene rearrangements are most common for tRNAs among metazoans in general, the mitochondrial genome rearrangements in Pectinidae often involve coding genes, unlike what has been observed in other animal groups. Malkócs et al [57] investigated the mitogenomic rearrangements observed in certain Pectinidae species and visualized their mitochondrial structural variations. Using the OrgaMiner workflow, we obtained annotations for three species within this family and compared them with published data (Figure 6 in Malkócs et al [45]).…”
Section: Classmentioning
confidence: 99%
See 1 more Smart Citation
“…While gene rearrangements are most common for tRNAs among metazoans in general, the mitochondrial genome rearrangements in Pectinidae often involve coding genes, unlike what has been observed in other animal groups. Malkócs et al [57] investigated the mitogenomic rearrangements observed in certain Pectinidae species and visualized their mitochondrial structural variations. Using the OrgaMiner workflow, we obtained annotations for three species within this family and compared them with published data (Figure 6 in Malkócs et al [45]).…”
Section: Classmentioning
confidence: 99%
“…Although the de novo-assembled chloroplast genomes from both the WGS and RNA-Seq data showed promising results, with many unique genes aligned and commonly found in the reference genomes, there were some inconsistencies observed between the reference genomes and OrgaMiner-assembled genomes, as the gene numbers and compositions differed more than expected. This difficulty may have arisen due to the challenging nature of annotating plastid genomes, a task that requires manual curation, which users may contemplate following the assembly of plastid genomes [57].…”
Section: Applicability Of Orgaminer Workflow Across Different Cladesmentioning
confidence: 99%